First record of Trypauchen vagina (Bloch and Schneider 1801) (Perciformes: Gobiidae) in the Narmada River, Gujarat, India - Nevya Thakkar; Kangkan Jyoti Sarma; Pradeep C Mankodi (Journal of Fisheries, 2018)
Gobiids are a large group of fishes inhabiting freshwater, marine and brackish water habitats. Trypauchen is the Indo-Pacific genus and comprises of two species: Trypauchen pelaeos known from Myanmar, Malaysia, Thailand, Vietnam and China; and T. vagina, distributed from Kuwait, along the coasts of India, ranging eastward to the Philippines, Taiwan and China. A specimen of T. vagina (Bloch and Schneider 1801) was caught by cast net from the shallow water of the Narmada River on 11 April 2017 that has later been preserved in the museum of Department of Zoology, Faculty of Science, The Maharaja Sayajirao University of Baroda, Vadodara (voucher number: ZL-CH-OSH-026). This paper presents the first observation of T. vagina in the Narmada River in Gujarat.